PERBEDAAN PUTUSAN PRAPID P.N. TARUTUNG NO. 6/PID.PRA/2020 DAN PUTUSAN PRAPID P.N. MEDAN NO. 5/PID.PRA/2021 - Jenda Riahta Silaban; Madiasa Ablisar; Sunarmi Sunarmi; Mahmud Mulyadi (Law Jurnal, 2023)
ABSTRACTDecision of the Constitutional Court of the Republic of Indonesia No. 21/PUU-XII/2014,date. 28/04/2015, expanded the prepid object regarding "the validity of the determinationof the suspect". One of the cases regarding testing the validity of the suspectdetermination in this study was between the Pre-Trial Decision at the Tarutung DistrictCourt No. 6/Pid.Pre/2020, date. 31/08/2020 which is different from the Medan DistrictCourt No. 5/Pid.Pre/2021, date. 16/02/2021 An. Petitioner "P.S.H". The problems are:Factors that influence the disparity in the pretrial decision on the determination of differentcorruption suspects in the Prapid P.N.Trt Decision. No. 6/Pid.Pra/2020 with the Decisionof Prapid P.N.Mdn. No. 5/Pid.Pre/2021; and Analysis of legal considerations for thedisparity of the pretrial decision. This research is normative legal research, which isdescriptive analysis in nature. The Investigating Prosecutor at the North SumatraProsecutor's Office has done this and corrected the entire series of investigations andinvestigations, so the determination of the suspect he has determined is appropriate anddeclared valid by the pretrial judge at the Medan District Court. In the context of theinvestigation conducted by the Attorney General's Office Investigator HumbangHasundutan, it was actually only an error in the administration of investigations andinvestigations. The administrative error, by setting the suspect first, instead of findingsufficient evidence as ordered by law. Determination of suspects should be carried outbased on Article 183 jo. Article 184 paragraph (1) of the Criminal Procedure Code jo.Article 422 Regulation of the Attorney General of the Republic of Indonesia No. PERJA-039/A/JA/10/2010 concerning Administrative and Technical Management of Cases ofSpecial Crimes.Keywords: Pretrial; The validity of the determination of the suspect; District Court.